Design of rubble-mound structure as scour protection for vertical seawalls: layer thickness, median rock mass and energy through the layers - Streuderst, Anchen (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.